Existence and Convergence of Fixed points of Generalized alpha non-expensive mappings in metric spaces: Existence and Convergence of Fixed points of Generalized alpha non-expensive mappings - Asghar, Ali; Chowdhury, Mohammad Showkat Rahim; Muhammad, Noor; Aslam, Muhammad Suhail (Scientific Inquiry and Review, 2022)
We give certain conditions about different kinds of mappings. These conditions will be median of non-expansive mappings and quasi-non-expansive mappings. We will establish some fixed point results of some generalized non-expansive mappings in metric spaces. Moreover, we will also establish few existence and convergence results about generalization of non-expansive mappings. Finally, we present some useful lemmas and propositions.